Intracardiac vs. transesophageal echocardiography guided transcatheter closure of patent foramen ovale and atrial septal defects - Shatla, Islam; Kennedy, Kevin; Saxon, John Thomas; Chhatriwalla, Adnan K.; Magalski, Anthony; Lehenbauer, Kyle; Abdelkarim, Islam; Huber, Kenneth Christopher; Huded, Chetan P. (Cardiovascular revascularization medicine, 2025)
Transcatheter closure of atrial septal defects (ASD) and patent foramen ovale (PFO) can be performed with transesophageal echocardiography (TEE) or intracardiac echocardiography (ICE) guidance, but data comparing both modalities in contemporary practice is lacking. Using ICD-10 codes, patients who underwent transcatheter ASD/PFO closure between 2016 and 2020 using ICE or TEE in the Nationwide Readmissions Database (NRD) were identified. Propensity-score matching was performed to compare in-hospital adverse events, length of stay (LOS), cost, and 30-day non-elective readmissions. A total of 964 patients underwent ASD/PFO closure with ICE (38.3 %, n = 369) or TEE (61.7 %, n = 595) between 2016 and 2020. Propensity score matching yielded 327 patients in each group, which were well balanced. Median (IQR) age was 59.0 (46.0, 72.0) years and 54.7 % were female. No difference was observed in the rate of in-hospital major adverse events between groups. ICE guidance was associated with a lower median cost (ICE $20,140.1 (14,622.3, 25,027.0) vs TEE $20,740.4 (14,137.5, 33,045.3), p < 0.04). In conclusion, ICE guided ASD/PFO closure was associated with lower hospitalization cost without increasing in-hospital adverse events when compared with TEE guidance. •ICE-guided transcatheter PFO/ASD closures had a safety profile similar to TEE guidance within the context of measured adverse outcomes.•Both ICE and TEE had similarly low rates of in-hospital adverse events, but costs were less with ICE.•These results are reassuring and support the adoption of ICE as a primary imaging modality for transcatheter PFO/ASD closures.